Meeting sustainable development goals: alternative extraction processes for fucoxanthin in algae - Foo, Su Chern; Khoo, Kuan Shiong; Ooi, Chien Wei; Show, Pau Loke; Khong, Nicholas M. H.; Md. Yusof, Fatimah (Frontiers Media, 2021)
The ever-expanding human population puts tremendous pressure on global food security. With climate change threats lowering crop productivity and food nutritional quality, it is important to search for alternative and sustainable food sources. Microalgae are a promising carbon-neutral biomass with fast growth rate and do not compete with terrestrial crops for land use. More so, microalgae synthesize exclusive marine carotenoids shown to not only exert antioxidant activities but also anti-cancer properties. Unfortunately, the conventional method for fucoxanthin extraction is mainly based on solvent extraction, which is cheap but less environmentally friendly. With the emergence of greener extraction techniques, the extraction of fucoxanthin could adopt these strategies aligned to UN Sustainable Development Goals (SDGs). This is a timely review with a focus on existing fucoxanthin extraction processes, complemented with future outlook on the potential and limitations in alternative fucoxanthin extraction technologies. This review will serve as an important guide to the sustainable and environmentally friendly extraction of fucoxanthin and other carotenoids including but not limited to astaxanthin, lutein or zeaxanthin. This is aligned to the SDGs wherein it is envisaged that this review becomes an antecedent to further research work in extract standardization with the goal of meeting quality control and quality assurance benchmarks for future commercialization purposes.